An implantation Diamond detector as a beam monitor for an intense radioactive ion beam. (December 2020) - Rojo, J S; Diget, C Aa; de Séréville, N; Assié, M; Lemasson, A; Ramos, D; Lohstroh, A; Reardon, C
Abstract: We present the characterization of a Diamond detector and its response as a beam rate monitor with full stopping of radioactive ion beams of high intensity. The detector has been implemented in the VAMOS focal plane at GANIL and utilised in conjunction with AGATA and MUGAST detector systems. In the present experiment, for the first time, the beam has been fully stopped, rather than being recorded by a transmission detector. The Diamond detector has been tested for use as a particle counter for monitoring a high intensity, radioactive ion beam in the study of the alpha transfer reaction 7 Li( 15 O, t) 19 Ne. The present experiment, which took place in July 2019, has used a 15 O radioactive beam with a high intensity of 10 7 particles per second due to the weak reaction population and it has been measured using the VAMOS spectrometer and the AGATA and MUGAST arrays. Detailed monitoring of beam intensities in the range of 10 6 – 10 7 particles per second is particularly challenging in radioactive ion beam experiments. Thus, the chosen method involves the diamond detector due to its sub-nanosecond response time as well as its radiation hardness. The study of the alpha transfer reaction 7 Li( 15 O, t) 19 Ne will be performed to determine the radiative alpha capture rate on 15 O which is a key breakout route from the Hot-CNO cycle which leads to a explosive nucleosynthesis in X-ray bursts.